IMPLEMENTATION OF THE COLLABORATIVE PROBLEM-SOLVING LEARNING MODEL USING GEOGEBRA ON THE MATHEMATICAL COMMUNICATION ABILITY AND CONFIDENCE OF MTS ISLAMIYAH CIOMAS STUDENTS - Salva, Ratu; Hamidah, Hamidah; Ayuningtyas, Vidya; Kusuma, Jaka Wijaya (Yayasan Education and Social Center, 2024)
One of the low cognitive and affective abilities of students is mathematical communication skills and self-confidence. This study aims to determine the difference in mathematical communication skills and students' confidence between those who use the Collaborative problem-solving model with the Geogebra application and those who use the lecture method. The research design used in this study is actual experimental design. Sampling in this study was carried out randomly, namely classes VIIIA and VIIIB. The data collection technique uses a mathematical communication ability test and a student confidence questionnaire. Data analysis was carried out by prerequisite tests (normality and homogeneity tests), hypothesis tests, and t-tests. From the results of the t-test data posttest of students' mathematical communication skills, a score of sig. (2-tailed) 0.047 < 0.05, so it was concluded that there was a difference in the mathematical communication ability of students in the experimental and control classes. The average result of the confidence questionnaire of students in the experimental class was 75.75, while in the control class, it was 55.80, so it was concluded that the student's confidence in the experimental class was better than that of the control class